2017
DOI: 10.1016/j.nicl.2017.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Advanced magnetic resonance imaging and neuropsychological assessment for detecting brain injury in a prospective cohort of university amateur boxers

Abstract: Background/aimThe safety of amateur and professional boxing is a contentious issue. We hypothesised that advanced magnetic resonance imaging and neuropsychological testing could provide evidence of acute and early brain injury in amateur boxers.MethodsWe recruited 30 participants from a university amateur boxing club in a prospective cohort study. Magnetic resonance imaging (MRI) and neuropsychological testing was performed at three time points: prior to starting training; within 48 h following a first major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
3
1
2
Order By: Relevance
“…Contrary to a recent study by Hart et al (Hart et al, 2017), this study found lower cortical thickness in the right cuneus in impaired boxers. Our findings are in agreement with a couple of studies with mTBI participants (Govindarajan et al, 2016;Santhanam et al, 2019) where cortical thinning in cuneus has been reported due to mTBI.…”
Section: 1: Cortical Thickness and Its Role In Rhicontrasting
confidence: 99%
“…Contrary to a recent study by Hart et al (Hart et al, 2017), this study found lower cortical thickness in the right cuneus in impaired boxers. Our findings are in agreement with a couple of studies with mTBI participants (Govindarajan et al, 2016;Santhanam et al, 2019) where cortical thinning in cuneus has been reported due to mTBI.…”
Section: 1: Cortical Thickness and Its Role In Rhicontrasting
confidence: 99%
“…The study by Hart et al. (35) also found no statistical differences in DTI-derived FA and MD values using TBSS between control and university amateur boxers. Thus, the present study suggested the MK parameter was more sensitive than DTI parameters including FA and MD parameters in detecting brain microstructural changes after mTBI.…”
Section: Discussionmentioning
confidence: 88%
“…No obstante, respecto a los cambios cognoscitivos asociados a la práctica del boxeo aficionado existe controversia. Algunos estudios señalan que hay evidencia de disfunción en procesos cognitivos: atención, memoria de trabajo y tiempos de reacción (Hart et al, 2017;Roozbahani, 2015;Warden et al, 2001), por el contrario, otros estudios señalan que no existen alteraciones neuropsicológicas en tareas que evalúan la atención sostenida, atención selectiva, memoria, resolución de problemas y tiempos de reacción (Khani et al, 2012;Lesiakowski et al, 2013;Stojsih et al, 2010). Es posible que estas contradicciones puedan deberse a varios factores entre los que se encuentran el hecho de que las disfunciones no son detectables con los instrumentos utilizados, a que los estudios no se han centrado en procesos cognitivos que pudiesen estar comprometidos, como es el caso de las Funciones Ejecutivas (FE), a que no se ha controlado algunas variable como el tiempo de práctica del boxeo, el peso, edad de los boxeadores, y otros factores que se sabe son protectores contra el daño cerebral como es el nivel educativo.…”
Section: Introductionunclassified